2005
DOI: 10.1037/0022-3514.89.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Don't worry, be happy? Neuroticism, trait-consistent affect regulation, and performance.

Abstract: People regulate their affect either to feel good or to achieve instrumental success. The present experiments show that when driven by performance goals, people can be motivated to experience unpleasant affect when it is trait-consistent, because of its instrumental benefits (e.g., M. Tamir & M. D. Robinson, 2004). In 4 studies, individuals high in neuroticism were more likely than those low in neuroticism to choose to increase their level of worry, as indicated by self-reported preferences (Study 1) and by beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
196
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(219 citation statements)
references
References 58 publications
17
196
1
5
Order By: Relevance
“…For example, avoidance motivation appears to be more common and also less harmful in collectivistic cultures than individualistic cultures (e.g., for a review, see Hamamura & Heine, 2008; for a counterpoint perspective, see Elliot et al, 2012), and also among neurotics and defensive pessimists than optimists (Norem & Illingworth, 1993;Tamir, 2005). A parallel pattern seems possible for late adulthood (cf.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…For example, avoidance motivation appears to be more common and also less harmful in collectivistic cultures than individualistic cultures (e.g., for a review, see Hamamura & Heine, 2008; for a counterpoint perspective, see Elliot et al, 2012), and also among neurotics and defensive pessimists than optimists (Norem & Illingworth, 1993;Tamir, 2005). A parallel pattern seems possible for late adulthood (cf.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…On the basis of our results, it is further possible that people strategically put themselves in a positive mood to secure success at self-control, for example, by bringing to mind positive thoughts before undergoing an unpleasant medical checkup. Thus, as much as previous research has suggested that people sometimes seek out a negative mood to facilitate performance on specific tasks (Tamir, 2005;Tamir & Robinson, 2004), it is possible that they also seek a positive mood to ensure success in general.…”
Section: Mood As a Goal Versus A Resourcementioning
confidence: 98%
“…There is research to suggest that individuals higher in neuroticism are more likely to experience worry in cognitively demanding situations, to improve performance and to have impaired cognitive reappraisal by demonstrating a trait congruent and emotionally charged appraisal of situations, which means perceiving situations in a negative and emotionally charged way [20]. Research has also revealed that cognitive reappraisal can replace negative stress with positive stress.…”
Section: Worry and Emotional Regulation Of Body Experiencesmentioning
confidence: 99%
“…It is proposed that a measure that taps into general and specific concerns about physical sensations should draw from previous research that looks not only at the links between neuroticism and worry [8] but also at the links between neuroticism, affect related emotional regulation and stress [20].…”
Section: Worry and Emotional Regulation Of Body Experiencesmentioning
confidence: 99%